The Effects of Communicative Approach on Learners Foreign Language Proficiency Levels by Using the Needs Analysis in English for Specific Purposes Classes - Çağda Kıvanç Caganaga (International Online Journal of Education and Teaching, 2014)
The purpose of this study is to analyse the Effects of Communicative Approach on learners foreign language proficiency levels by using the needs analysis in English for Specific Purposes in faculty first year classes. The population of the present study includes 160 students who study in the first year faculty English program of English Preparatory School of European University of Lefke. Subjects of the study were selected randomly. Demographic characteristics of the subjects are the students’ field of study, age, gender, students’ native language, foreign language level of the students, the frequency of students use of English for work or studies and their knowledge about the field. Three different data collection method was used in this study. As a way of data collection that can be used in the study of needs analysis, questionnaires and interviews were used. For students questionnaire and for teachers interviews were used. For the second step of the study, Cambridge proficiency test which was developed by Cambridge University Press in accordance with the Council of Europe was applied as a pre test and post test. The research data were analyzed by using the SPSS statistical package program. At the end of the study, the students reported a positive opinion on all aspects of the ESP program which was re-designed and applied differently. Students’ proficiency level improved based on the approach and teaching program.